Lesions of the hypothalamus and pituitary inhibit volume-expansion-induced release of atrial natriuretic peptide - Antunes-Rodrigues, J. (1991)
Expansion of the blood volume causes a release of atrial natriuretic peptide (ANP) that is believed to be important in induction of the subsequent natriuresis and diuresis which, in turn, acts to reduce the increase in blood volume. Since stimulation of the anteroventral portion of the third cerebral ventricle (AV3V) induced a rapid elevation of plasma ANP, whereas lesions of the AV3V were followed by a marked decline in plasma concentration of the peptide, we hypothesized that release of ANP from the brain ANP neuronal system might be important to the control of plasma ANP. The perikarya of the ANP-containing neurons are densely distributed in the AV3V and their axons project to the median eminence and neural lobe. To test the hypothesis that these neurons are involved in volume-expansion-induced ANP release, by using electrolysis we destroyed the AV3V, the site of the perikarya, in male rats. Other lesions were made in the median eminence and posterior pituitary, sites of termination of the axons of these neurons, and also hypophysectomy was performed in other animals. In conscious freely moving animals, volume expansion and stimulation of postulated sodium receptors in the hypothalamus were induced by injection of hypertonic NaCI solution [0.5 or 0.3 M NaCl; 2 ml/100 g (body weight)]. Volume expansion alone was induced with the same volume of an isotonic solution (NaCl or glucose). In the sham-operated rats, volume expansion with hypertonic or isotonic solutions caused equivalent rapid increases in plasma ANP that peaked at 5 min and returned nearly to control values by 15 min. Lesions caused a decrease in the initial levels of plasma ANP on comparison with values from the sham-operated rats, and each type of lesion induced a highly significant suppression of the response to volume expansion on testing 1-5 days after lesions were made. Because a common denominator of the lesions was elimination of the brain ANP neuronal system, these results suggest that the brain ANP plays an important role in the mediation of the release of ANP that occurs after volume expansion. Since the content of ANP in this system is much less than that in the atria, there must be a remarkable increase in synthesis and release of brain ANP associated with this stimulus. It is also possible that blockade of volume-expansion-induced release of other neurohypophyseal hormones, such as endothelin, may block release of ANP from atrial inyocy tes. It is probable that volume expansion detected by stretch of atrial and carotid-aortic baroreceptors causes afferent input to the brain ANP system, thereby causing increased release of the peptide from the median eminence and neural lobe. Our results emphasize the importance of brain ANP to the control of ANP release to the blood.